Communication versus (Restricted) Delegation: An Experimental Comparison - Silvia Dominguez-Martinez; Randolph Sloof (Tinbergen Institute, 2016)
This paper reports the results from a laboratory experiment investigating a manager's decision whether or not to delegate authority to a better informed worker whose interests are often, but not always, congruent. Keeping authority implies a loss of information, as the worker communicates his information strategically. Delegating authority leads to a loss of control. A key aspect of our design is that the manager can restrict the worker's choice set when delegating authority. We find that, in case of delegation, managers (as predicted) put tighter restrictions when interests are less aligned. Workers send more informative messages under communication than predicted by the pure strategy equilibria. This finding neither appears to be driven by lying aversion of workers nor by credulity of managers. Qualitatively, our results are in line with a mixed strategy equilibrium under communication, which strictly outperforms optimal restricted delegation and is relatively close to the optimal stochastic mechanism in our setting.
Keywords: C90; D80; M20; 330; Delegation; Communication; Laboratory Experiment; Organizational Economics